Building sister chromatid cohesion: smc3 acetylation counteracts an antiestablishment activity. - Rowland, B; Roig, M; Nishino, T; Kurze, A; Uluocak, P; Mishra, A; Beckouët, F; Underwood, P; Metson, J; Imre, R; Mechtler, K; Katis, V; et al. (2009)
Cohesin's Smc1, Smc3, and Scc1 subunits form a tripartite ring that entraps sister DNAs. Scc3, Pds5, and Rad61 (Wapl) are regulatory subunits that control this process. We describe here smc3, scc3, pds5, and rad61 mutations that permit yeast cell proliferation and entrapment of sister DNAs by cohesin rings in the absence of Eco1, an acetyl transferase normally essential for establishing sister chromatid cohesion. The smc3 mutations cluster around and include a highly conserved lysine (K113) close to Smc3's ATP-binding pocket, which, together with K112, is acetylated by Eco1. Lethality caused by mutating both residues to arginine is suppressed by the scc3, pds5, and rad61 mutants. Scc3, Pds5, and Rad61 form a complex and inhibit entrapment of sister DNAs by a process involving the "K112/K113" surface on Smc3's ATPase. According to this model, Eco1 promotes sister DNA entrapment partly by relieving an antiestablishment activity associated with Scc3, Pds5, and Rad61.